Improving Satisfaction and Loyalty of Online Shop Customer Based on E-Commerce Innovation and E-Service Quality - Sarli Rahman; Fadrul Fadrul; Mujtaba M Momin; Yusrizal Yusrizal; Robert Marlyn (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
The purpose of this study is to develop new knowledge related to innovation in e-commerce, which we call e-commerce innovation, and how its impact on customer satisfaction and loyalty, together with e-service quality, in the context of an online shop in Indonesia. Several measurement items of e-commerce innovation were adopted and modified from the existing literature. To answer how the impact on customer satisfaction and loyalty, then used partial least squares structural equation modeling to analyze data from 400 respondents. Empirical test results found that e-commerce innovation and e-service quality can each increase customer satisfaction and loyalty. It is also known that in the context of online shop customers in Indonesia, its easier to create customer satisfaction than customer loyalty.